Vocabulary learning strategies and vocabulary size of pre-university ESL learners - Muhamad, Ainon Jariah; Engku Ibrahim, Engku Haliza; Achoui, Sana (2014)
Knowing the importance of vocabularies and vocabulary learning strategies (VLS), this study attempts to determine the vocabulary size of pre-university students and their preferred vocabulary learning strategies (VLS). The aim of this study was to examine the vocabulary learning strategies used by pre-university ESL learners and to investigate if there is any relationship between the learners’ vocabulary learning strategies on the vocabulary size. It also investigates if there is any effect of the vocabulary learning strategies on the vocabulary size of these ESL learners. 128 pre-university students (level 6 students – upper intermediate level) taking an intensive English course at the Centre for language and Pre-university development (CELPAD) were involved in the study. A vocabulary learning questionnaire based on Schmitt’s taxonomy (1997) and a vocabulary test based on Nation’s (2001) vocabulary size were used for data collection. The results of this study suggest that the ESL pre-university students preferred the discovery meaning category which was essential for their vocabulary development and learning. The most used strategies were “guessing the meaning of a new word from context” and “the use of the English-language media” while the least preferred strategy was “ask English teacher to check my flash cards or word lists for accuracy”. Results also showed that the majority (64.8%) of students were considered as intermediate learners with vocabulary size score range of 6100-8100. Nevertheless, the most important finding of this study reveals that from the 58 strategies, only four strategies showed correlation and significant contributions (p<0.05) towards the learners’ total vocabulary size.